Trends in the epidemiology, diagnosed age and mortality rate of haemophiliacs in Taiwan: a population‐based study, 1997–2009. (29th January 2014) - Chang, C.‐Y.; Yeh, G.‐C.; Lin, S.‐Y.; Tseng, I.‐J.; Tsai, C.‐H.; Lee, Y.‐W.
Summary: Many studies on epidemiology and mortality in haemophiliacs have been published in Western countries. However, few have been conducted in Asian countries. The purpose of our study was to investigate the nationwide epidemiology and mortality of haemophiliacs in Taiwan. Population‐based data from the National Health Insurance Research Database between 1997 and 2009 were analysed using SAS version 9.3. The annual prevalence of haemophilia A (HA) and haemophilia B (HB) increased steadily to 7.30 and 1.34 cases per 100000 males, respectively, in 2009. The annual crude incidence of HA and HB averaged 8.73 and 1.73 per 100000 male births respectively. During the study period, the proportion of paediatric haemophiliacs decreased from 41.5% to 28.2% and the proportion of geriatric haemophiliacs increased from 2.5% to 5.7%. Among 493 newly diagnosed cases, the peak diagnostic ages were before 3 and between ages 10 and 40. Of the 76 cases of mortality, most patients died between the ages of 18 and 60. However, an increase in the age of mortality was noted after 2005 ( P  = 0.033). The overall standardized crude death rate of haemophiliacs was 10.2 per 1000 people, and the standard mortality ratio was 1.98. The annual prevalence of human immunodeficiency virus infection in haemophiliacs grossly declined from 1998 to 2009, with an average of 32.2 per 1000 haemophiliacs. This was a rare population‐based study on the epidemiology and mortality of haemophilia in a Chinese population and Asian countries. The 13‐year trends showed advances in haemophilia care in Taiwan.